The Impact Of Severity Of Ischaemia In Acute Coronary Syndrome On The Extent Of Coronary Artery Disease At Angiography The Role Of Past Ischaemia - Hassan Yousif Al-Najjar (مجلة كلية الطب, 2006)
Background: Clinical classification of patients with acute coronary syndrome is essential step in identifying severe cases before referring them, fairly quickly, for the ultimate investigation of coronary angiography .Hence it is important to find out the extent at which the severity of the disease, based on clinical classification, agrees with its severity at angiography and to see whether traditional Risk factors or pas ischaemia played a role. Patients and Methods : The angiographer data of 178 consecutive pts with Acute Coronary Syndrome (ACS) were retrospectively analyzed. The pts consisted of 114 with Unstable Angina (UA)  and 64 pts with Non-ST-Segment Elevation Myocardial Infarction (NSTEMI). Patients were classified depending upon the predominating clinical assessment during hospitalization into four groups of progressively worsening ischaemia. They were; group 1; New onset Angina; 27 pts, group 2; Deteriorating Chronic Angina, 33 pts, group 3; Rest Angina 54 pts, and, group 4; Non-ST-Elevation Myocardial Infarction (NSTEMI), 64 pts. Results : Coronary Angiography revealed that the frequency of multi-vessel coronary Disease (MVD) in group 1, 2, 3, and 4 were 48%, 73%, 72%, and 56% respectively which meant that worsening of ischaemia was not accompanied by commiserate increase of the frequency of MVD in Rest angina and NSTEMI. To explain that we calculated the average number of Five traditional Risk Factors; Hyperlipidaemia (HL), Diabetes Mellitus (DM), Hypertension (HTN), Smoking (SM), and Positive Received March 2006 Family History (PFH) in the four groups ofACS (R.F. score) and they were 1.72, 1.87, 2.13, 2.51 in Accepted May 2006 groups 1,2,3, and 4 respectively. Then we studied the relation of having one, two, three, and four orfive Risk Factors and the frequencies of Multi-vessel disease and they were; 43%, 67%, 76%, and 84% respectively which meant that the frequency of MVD ought to increase from group 1 to group 4 supporting the clinical classification. This prompted us to look into the individual Risk factors. The clinical data showed that the incidence of HL had risen significantly in Ch. D. angina and Rest Angina (P: 0.03) and that the incidence of SM had risen significantly in NSTEMI (P.• 0.001). Since the angiographic data had demonstrated a significant association of HL with MVD and SM with SVD we may understand why the rate of MVD was not higher  in NSTEMI than UA. To explain why the frequency of MVD in Rest Angina (g. 1) was not higher than Ch. D. Angina (g. 2) despite having worse ischaemia and higher R.F. Score we scrutinized the data and noticed that the main difference between group 1 and group 2 that chronic stable angina had preceded the onset of UA in Group 2 while it did not do in group 1. On the other hand Rest Angina and NSTEMI pis were a mixture of those with and without prior ischaemia. To follow this point further we divided both groups into two subgroups: one with history of prior ischaemia and one without it. The frequency of MVD in Rest Angina and NSTEMI with prior ischaemia were 83%% and 81 %% compared to 54% and 39% respectively in pts without it. Conclusion this study has shown that clinical classification in Acute Coronary Syndrome may predict severity of the underlying CAD to some extent however considering the no. Of risk factors and which Risk factor and whether there was antecedent ischaemia would improve the prediction a great deal.